2022
DOI: 10.1093/pch/pxab100
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID-19 on poisonings in the paediatric emergency department

Abstract: Objectives The purpose of this study is to describe the impact of the pandemic on poisoning in children under 18 years presenting to a tertiary care paediatric emergency department (ED) in Canada. Methods We utilized the Canadian Hospitals Injury Reporting and Prevention Program (CHIRPP) surveillance data to identify children presenting to the Hospital for Sick Children for poisonings during two time periods: pre-pandemic (Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…This might be explained by the increase of laws and restrictions that were implemented during the lockdown to limit the rate of the disease spread. In contrast, Zhang et al and Raffee et al showed an increase in poisoning cases during the pandemic [ 11 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the increase of laws and restrictions that were implemented during the lockdown to limit the rate of the disease spread. In contrast, Zhang et al and Raffee et al showed an increase in poisoning cases during the pandemic [ 11 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, French data state that gel dispensers often are close to children's faces leading to corneal lesions [18].Furthermore, South Africa highlighted a 60% increase in calls regarding exposure to antiseptics compared to pre-pandemic time [19]. A rise in poisonings has also been seen in Canada, probably associated with the school closure and homestay during the lockdown [12]. An Italian study highlighted that the most frequent poisons during the pandemic were medications and hand sanitizers [20].…”
Section: Discussionmentioning
confidence: 99%
“…8 However, the introduction of edible cannabis in Canada coincided closely with the COVID-19 pandemic when there were large changes in pediatric health care visit patterns, including reports of increases in pediatric poisoning events. 9,10 Consequently, whether pediatric poisonings have increased primarily as a result of the legalization of recreational cannabis in general, an increase in children's access to ready-to-consume commercially produced legal cannabis edibles, COVID-19-related factors, or a combination of factors is unclear. Also unclear is how temporal trends in cannabis poisonings differ from all-cause pediatric poisonings and the relative burden of cannabis on poisoning events in children.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from Canada found that ED visits and hospitalizations for cannabis poisonings in children increased after legalization of recreational cannabis, particularly when legal cannabis edibles were introduced . However, the introduction of edible cannabis in Canada coincided closely with the COVID-19 pandemic when there were large changes in pediatric health care visit patterns, including reports of increases in pediatric poisoning events . Consequently, whether pediatric poisonings have increased primarily as a result of the legalization of recreational cannabis in general, an increase in children’s access to ready-to-consume commercially produced legal cannabis edibles, COVID-19–related factors, or a combination of factors is unclear.…”
Section: Introductionmentioning
confidence: 99%